Examining the Relationship between Selfies, Adolescents and Archetypes: The Psychology of Taking Selﬁes and their Consequences on the Adolescent Self-Conscious - Merwe, Petro van der (International Journal of Criminology and Sociology, 2021)
This study explores the attitudes of adolescents in South Africa towards selfie-taking as well as the effects that the selfie has on the consciousness of their shadow. The aim is to contribute to understanding the current impact of this phenomenon on adolescents. Social media, through the use of selfies, can encourage self-promotion and create an obsession with one’s physical appearance. Adolescents mostly shape their self-concepts based on their understanding of how others view them. The informants comprised 58 learners from three secondary schools in Tshwane (Gauteng). The data collection methods used were semistructured interviews and observation methods. This research study resonates with the looking-glass-self perspective, which highlights the importance of the evaluation of others to the development of the self-conscious. Technology constantly evolves and grows, a theoretical implication of which is the need to continue exploring selfies as a means for the search of identity. Regardless, in raising the question of what selfies, adolescents, and archetypes have in common, this article succeeds in bringing together this rather recent concept, the area of scientific enquiry related to selfies, and a psychological construct coined by the founder of analytical psychology, Jung, that is so well established in the sciences and steeped in thoughts of wisdom that it has stood the test of time. In doing so, the article taps into not only developmental psychology but also social psychology and sociology, the study of human social relationships.